2021
DOI: 10.1155/2021/1103631
|View full text |Cite
|
Sign up to set email alerts
|

Role of Pretreatment Hemoglobin-to-Platelet Ratio in Predicting Survival Outcome of Locally Advanced Nasopharyngeal Carcinoma Patients

Abstract: Background. The three-year survival rate of locally advanced nasopharyngeal carcinoma (NPC) patients in Indonesia is lower than in other Asian countries. Calculation of hemoglobin-to-platelet ratio (HPR) may become a more practical predictor than the ratios using leukocyte cell components. Yet, no study has been conducted to investigate the potential of HPR in predicting survival outcomes in locally advanced nasopharyngeal cancer patients. Objective. To determine the role of pretreatment hemoglobin-to-platelet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Our findings are in accordance with those of Mo et al 20 A previous study used HPR to predict overall survival in locally advanced nasopharyngeal cancer, concluding that low HPR was associated with poor 3-year overall survival. 12 Similarly, we found that low pre-operative HPR was linked to worse clinicopathological features, including increased depth of invasion, more lymph node metastasis, more advanced tumor stage, and larger tumor size.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Our findings are in accordance with those of Mo et al 20 A previous study used HPR to predict overall survival in locally advanced nasopharyngeal cancer, concluding that low HPR was associated with poor 3-year overall survival. 12 Similarly, we found that low pre-operative HPR was linked to worse clinicopathological features, including increased depth of invasion, more lymph node metastasis, more advanced tumor stage, and larger tumor size.…”
Section: Discussionmentioning
confidence: 51%
“… 8 11 Patients with malignant tumors often exhibit anemia, and a reduced hemoglobin–platelet ratio (HPR) is related to poor clinical outcomes in nasopharyngeal carcinoma and renal cell carcinoma. 12 , 13 Carcinoembryonic antigen (CEA) is a member of the immunoglobulin superfamily that acts as an intracellular adhesion molecule. 14 Currently, CEA is the most important common serum biomarker for detecting and monitoring colon cancer but its sensitivity and specificity are insufficient.…”
Section: Introductionmentioning
confidence: 99%